SWOT ANALYSIS OF COMPETITIVE ADVANTAGES STRATEGY ‘KARAWO’ HANDICRAFT INDUSTRY IN GORONTALO CITY: SWOT ANALYSIS OF COMPETITIVE ADVANTAGES STRATEGY ‘KARAWO’ HANDICRAFT INDUSTRY IN GORONTALO CITY - Idris Yanto Niode; Herwin Mopangga; Andi Yusniar Mendo (Bajang Institute, 2022)
This study aims to 1). analyze and find out what factors affect the internal and external environment in order to maintain the competitive advantage of SMI, Karawo handicraft industry ?; 2). find out and analyze what efforts were made by both business people (SMI) and local governments in order to maintain and support competitive advantage from SMI, Karawo handicraft industry in Gorontalo City; 3). analyze the competitive advantage strategy that is carried out by every SMI in Gorontalo city in winning the competition. The method used in this study is a survey method by conducting data collection techniques through interviews, observation and through questionnaires. The assessment is carried out by identifying the current internal and external environment so as to achieve the conditions expected in the future related to the competitive advantage strategy of the Karawo handicraft industry in Gorontalo City. To analyze these factors in order to formulate a competitive advantage strategy for SMI, especially the Karawo handicraft industry, it is carried out with a SWOT Analysis approach. The results show that the strategy to achieve the competitive advantage of the furniture industry in Gorontalo in the future can be done with Turnaround strategy, namely the way the internal approach can be done is by shortening the production chain that has been producing Karawo embroidery requires different skills and craftsmen. through this strategy or stage, it can be done by one of the craftsmen. The second stage is externally through a process of training and mentoring by universities, local governments and entrepreneurs to conduct training for mothers, the younger generation to train the process of slicing and embroidering in other words creating new craftsmen and fostering the interest of young people to like and use products The Karawo.